Disorder Engineering in Monolayer Nanosheets Enabling Photothermic Catalysis for Full Solar Spectrum (250–2500 nm) Harvesting. (30th October 2018) - Yang, Min‐Quan; Shen, Lei; Lu, Yuyao; Chee, See Wee; Lu, Xin; Chi, Xiao; Chen, Zhihui; Xu, Qing‐Hua; Mirsaidov, Utkur; Ho, Ghim Wei
Abstract: A persistent challenge in classical photocatalyst systems with extended light absorption is the unavoidable trade‐off between maximizing light harvesting and sustaining high photoredox capability. Alternatively, cooperative energy conversion through photothermic activation and photocatalytic redox is a promising yet unmet scientific proposition that critically demands a spectrum‐tailored catalyst system. Here, we construct a solar thermal‐promoted photocatalyst, an ultrathin "biphasic" ordered–disordered D‐HNb3 O8 junction, which performs two disparate spectral selective functions of photoexcitation by ordered structure and thermal activated conversion via disordered lattice for combinatorial photothermal mediated catalysis. This in situ synthetically immobilized lattice distortion, constrained to a single‐entity monolayer structure not only circumvents interfacial incompatibility but also triggers near‐field temperature rise at the catalyst–reactant complexes' proximity to promote photoreaction. Ultimately, a generic full solar conversion improvement for H2 fuel production, organic transformation and water purification is realized.